The reality of using modern digital technologies in managing global sports institutions - Saleh, Husam Malik (Universitas Tanjungpura, 2025)
Background. The rapid evolution of digital technologies has significantly impacted various sectors, including international sports organizations. These technologies offer vast potential to enhance both administrative and technical operations across diverse sporting disciplines. Objectives. This research aimed to explore the current state of modern digital technology adoption among international sports organizations and to identify the key challenges hindering their implementation. Methods. A mixed-methods approach was adopted, combining both quantitative and qualitative techniques for data collection and analysis. The study also employed a case study methodology focusing on prominent international organizations such as FIFA, UEFA, major European and Asian clubs, and national federations. The research examined relevant digital technology theories and categorized their applications within the sports sector. Results. The findings revealed that the swift advancement and deployment of digital technologies have significantly improved operational efficiency and innovation across sports organizations. However, challenges remain in terms of integration, resource allocation, and strategic collaboration. Conclusion. Digital technologies play a transformative role in global sports management. It is recommended that international sports organizations collaborate more closely with technology companies to establish strategic partnerships that foster service improvement, knowledge exchange, and sectoral development.